Agro-Climatic Characterization of Two Selected Stations in the Southern West Bengal, India - Banerjee, Saon; Mukherj, Asis; Mukhopadhayal, Apurba; Saikia, B; Bandyaopadhaya, S; Chatterjee, Sudeep (Journal of Science Foundation, 2013)
Maximum temperature, minimum temperature and rainfall data of Bankura (1992-2007) and Canning (1960-2006) were analyzed for assessing climatic trend and agro-climatic characterization of red-lateritic and coastal Zones of West Bengal respectively. These two zones are the most vulnerable regions to climate change in West Bengal, hence selected for the present study. While average values of annual maximum temperature and annual minimum temperature were used for climatic trend analysis, no definite trend was observed. So, maximum temperature of the hottest month and minimum temperature of the coldest month were used for detecting climatic trend. The maximum temperature shows positive trend for both the stations. An increasing trend of annual rainfall was also observed. In case of agro-climatic characterization the agricultural draught, meteorological draught, seasonal rainfall and rainfall probability using Markov-chain model were analyzed for the said two stations. Kharif crops of Bankura encountered two years (2000 & 2005) agricultural draught within 2000 -2007, whereas kharif crops of Canning encountered agricultural draught in 2006 within the said period. Likewise, the deviation of seasonal rainfall and probability of two consecutive wet weeks with different levels (10, 20,30,40,50 and 60 mm) of weekly total rainfall was worked out. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14619 J. Sci. Foundation, 8(1&2): 49-54, June-December 2010